Systematic Literature Review: The Role of Government Institutions in Corporate Social Responsibility in Nigeria - Hassan, Abubakar Isah; Mansor, Norma Binti; Abdullah, Nurhidayah Binti (International Journal of Psychosocial Rehabilitation, 2020)
Although Corporate Social Responsibility (CSR) initiatives have advanced considerably in the past few years. Despite the advancement in the literature on (CSR) very few of them have reflected on the roles of government institutions, especially in the emerging nations. The purpose of the review is to provide a systematic analysis of the role of government institutions on CSR. A methodical kind of literature review was carried out utilising approaches proclaimed by the Institute for Analyses and Propagations but adjusted to the specific requirements of this analysis. The basic tenets of institutional theory are equally employed in finding the role many institutions play in this exercise. The various online database was searched. The search phrases used were governments, CSR, Civil society organisation (CSOs). To be included, a paper requiresto incorporate a substantial explanation of the recognised function with or activities by the government or any of the institutions in reality. Articles that do not explain the real role of government institutions but only suggested are not included. The review studies are selected from 2009-2019. The total number of articles collected is one hundred and twenty-three (123) out of which sixty (60) of them were found worthy for the analysis. The functions of government institutions were recognised, particularly in the setting of facility deliverance and sustainable development, all together were described to be used to government institutions, CSR and CSOs research, and other activities. The functions described in the piece of work ought to enlighten all researchers in CSR that successful research in CSR cannot be realised without involving institutional theory.